Kinerja Alat Kondensasi Uap Air Laut Untuk Mendapatkan Air Murni - Tamrin Tamrin; Rivaldo Rivaldo; Warji Warji (The University of Lampung, 2021)
Testing of a greenhouse model condensation machine to purify the sea water needs to be developed to obtain fresh water. The purpose of this research is to transform seawater using solar energy by using the greenhouse effect principle This research uses testing machine performance to get pure water potential from sea water deselination. The test result of this machine has been able to vaporize seawater in one day ranging from 421 ml-814 ml, while water that can be harvested in one day ranges from 97.5 ml – 152.5 ml. The energy efficiency gained in this machine ranged from 21.22%-46.63%, while the efficiency of the evaporation result of this machine obtained the value ranged from 18.73%-24.85%. This machine has been able to convert seawater into fresh water by using the principle of greenhouse effect but still not able to work optimally.Keywords: fresh water, greenhouse effects, seawater